Self-realization of teacher: personal meaning and direction - Sergejko, Svetlana (Social Welfare: Interdisciplinary Approach, 2012)
On the basis of the study the problem of self-realization as a special type of activity taking into account the personal meaning of different types of teachers is revealed in the article. These results ascertained that the majority of modern Belarusian teachers do not possess the characteristics that contribute to their self-realization sufficiently. Relatively low rates were found in such important characteristics as internal locus of control, spontaneity, subjective well-being, positive temporal transspection, the value of development and self-realization, which makes it difficult to include teachers in self-realization activity. In the article also the typology of teachers according to the personal sense of self-realization, which can serve as a basis for finding ways to optimize selfrealization of educators, to identify the necessary conditions for the development of their self-realization activity has been identified.